2017
DOI: 10.1525/abt.2017.79.3.176
|View full text |Cite
|
Sign up to set email alerts
|

A Portable Augmented-Reality Anatomy Learning System Using a Depth Camera in Real Time

Abstract: In this paper, we present an augmented reality learning system that uses the input of a depth camera to interactively teach anatomy to high school students. The objective is to exemplify human anatomy by displaying 3D models over the body of a person in real time, using the Microsoft Kinect depth camera. The users can see how bones, muscles, or organs are distributed in their bodies without the use of targets for tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 12 publications
0
27
0
6
Order By: Relevance
“…There were three papers exploring the ARMM application; all were surveys directed at medical students and clinicians. [39][40][41] Responses from all three were positive. Varying majorities of respondents reported that ARMM increased learning motivation (58%), was beneficial in an educational setting (69.1%), stimulated active learning (82.4%), and improved 3-Dimensional understanding of anatomy (93.4%) while remaining easy to use.…”
Section: Anatomy Applications: Ar Magic Book (Various)mentioning
confidence: 97%
See 1 more Smart Citation
“…There were three papers exploring the ARMM application; all were surveys directed at medical students and clinicians. [39][40][41] Responses from all three were positive. Varying majorities of respondents reported that ARMM increased learning motivation (58%), was beneficial in an educational setting (69.1%), stimulated active learning (82.4%), and improved 3-Dimensional understanding of anatomy (93.4%) while remaining easy to use.…”
Section: Anatomy Applications: Ar Magic Book (Various)mentioning
confidence: 97%
“…Varying majorities of respondents reported that ARMM increased learning motivation (58%), was beneficial in an educational setting (69.1%), stimulated active learning (82.4%), and improved 3-Dimensional understanding of anatomy (93.4%) while remaining easy to use. 39,40 A large majority (80.5%) rated the system as excellent or good, and surveyed physicians unanimously recommended that ARMM be used to supplement existing anatomy curriculums. 41…”
Section: Anatomy Applications: Ar Magic Book (Various)mentioning
confidence: 99%
“…AR systems for anatomy education are still in its infancies. Several prototypes have been developed and studied with respect to their potential benefits for students (Kiourexidou et al, ; Küçük et al, ; Wang et al, ; Jain et al, ; Manrique‐Juan et al, ). Hackett and Proctor surveyed three‐dimensional displays and concluded that AR displays can have a positive impact on anatomy education (Hackett and Proctor, ).…”
Section: Introductionmentioning
confidence: 99%
“…A realidade aumentada vem sendo bastante utilizada como recurso tecnológico em ambientes educacionais. Diversos estudos comprovam que sua utilização traz contribuições para a percepção e motivação dos usuários em diversas atividades no contexto educacional, auxiliando na aprendizagem em diversas áreas do conhecimento (AYER; MESSNER; ANUMBA, 2016; MANRIQUE- JUAN, C. et al, 2017.). O alto nível de interatividade proporcionado pela realidade aumentada acarreta aprimoramento do aprendizado, além de permitir mais engajamento dos estudantes, principalmente quando envolvidos na criação de seus próprios projetos utilizando RA.…”
Section: Realidade Aumentada Na Educaçãounclassified